Impact of Watershed Development Programmes on Adoption of Crop Production Technologies - Om Prakash; Y.V.R. Reddy; G. Sastry; P. Srinivas Rao; H.P. Singh (Journal of Agricultural Extension Management, 2025)
Watershed Development Programme has been carried out on large scale in India, with an annual allocation of funds to the tune of about Rs.1000 crores, with an objective of developing and stabilizing natural resources in addition to improving productivity of crops, employment opportunities to rural people, income generation and standard of living of rural people in arid/ semi-arid regions in India. During the past three decades, many crop production technologies were evolved and spread to farmers’ fields. Since 1983-84, technologies of dryland crops were also transferred to farmers’ fields effectively on watershed basis, as technological options and choices available to dryland farmers are many and varied and it may be a problem for farmers to choose a package of technologies suitable to their fields